Taming the Leviathan or dismantling democratic government? Evolving political ideas on spontaneous income tax integration in the European Union - Jaakkola Jussi (Cambridge University Press, 2025)
By the turn of the 1990s, tax competition among national governments had emerged as a powerful law-making practice. The possibility of tax competition essentially depends on the design of transnational law, such as European law. This Article examines the change of economic, political, and legal ideas that have shaped responses by the European Communities and the European Union (EU) to income tax competition. It asserts that under the post-war settlement of embedded liberalism and moderate market integration, tax competition was not perceived as a fully developed phenomenon. Under increased cross-border economic mobility in the 1990s, tax competition became a critical concern but received a liberal and permissive reaction from the EU. In the 2010s, governing tax competition in the EU became a more vital topic. Still, in the contemporary EU, turning political ideas into legal rules capable of addressing tax competition remains hampered by the EU law requirement of unanimous decision-making. The European choice of whether and how to address tax competition involves profoundly contrasting ideas on the means by which to govern the socio-economic reality. The decision between spontaneous and regulated income tax integration is therefore a salient political question, but the unanimity rule undermines political contestation over tax competition and over the European model of fiscal federalism. The Article comes to a close by reflecting on whether the EU legal order offers means to overcome the deadlock of unanimity and whether it could accommodate a more properly political contestation over the Europeanisation of income taxation.